Students’ Perceptions of Learning Platform: The Advantages and Disadvantages of Quipper School - Izen Diva; Fauzul Etfita; Sri Wahyuni (J-SHMIC : Journal of English for Academic, 2022)
Quipper School is an online learning platform which consists of two portals, namely Learn for students and Link for teachers This research aimed to investigates the students‟ perception on the advantages and disadvantages of Quipper School platform in learning English. This research was conducted at SMAN 3 Mandau, and the sample was 52 students of the eleventh grade. This research used quantitative research, and the instrument is questionnaire. The questionnaire consists of 20 questions, divided into 10 questions of the advantages and 10 questions of the disadvantages. The results of this study were processed quantitatively using the Likert scale formula. The finding revealed the index advantages of 1st statement to the 10th statement were about between 60%-75%. The result indicates that students completely agree with the 10 questions of the advantages of Quipper School‟s. Equally important, the researcher also found that the students were dominant disagree with the 9 questions and were agree of 1 question of disadvantages of Quipper School‟s with the index 52%-61%. In conclusion, the students of SMAN 3 Mandau dominant disagree with the disadvantages of Quipper School and they assumed that Quipper School is an online learning platform that suitable for teachers and students in the learning process, especially in learning English.